The Wage Policy of a Firm when Recruitment is a Wage Dependent Poisson Process and Wages are Downward Rigid - Nils Henrik Schager (The Research Institute of Industrial Economics (IUI), 1986)
The paper contains an analysis of a firm's optimal wage and recruitment policy, when the dynamic labor supply to the firm is specified as a Poisson distributed flow of job-applicants, whose reservation wages are distributed in a fairly general way. Provided that the firm is not allowed to lower its wage level over time, it has recently been shown by the author that the optimal policy is to establish a constant wage level over future employment states. The paper explores the further properties of the optimal wage and its response to changes in the parameters of the decision problem.
Keywords: J30; 330; Recruitment; labour supply; optimal wage; wage rigidity; Lohnpolitik